2017
DOI: 10.4014/jmb.1605.05022
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Changes in Penicillium expansum Grown in a Medium Derived from Host Plant

Abstract: causes blue mold rot, a prevalent postharvest disease of pome fruit, and is also the main producer of the patulin. However, knowledge on the molecular mechanisms involved in this pathogen-host interaction remains largely unknown. In this work, a two-dimensional gel electrophoresis-based proteomic approach was applied to probe changes in 3.3703 cultivated in apple juice medium, which was used to mimic the in planta condition. The results showed that the pH value and reducing sugar content in the apple juice med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Recently, we have demonstrated that the general inductor of fungal secondary metabolism biosynthesis, LaeA, is required for the production of not only patulin, but also other putative SMs produced by P. expansum , and contributes to virulence on apples (Kumar et al., ). In addition to LaeA, other regulatory proteins known to impact natural product biosynthesis in fungi, including transcription factors CreA, AreA and PacC associated with broad responses to carbon availability, nitrogen availability and pH, respectively, have been shown to be expressed during the biosynthesis of patulin, which is significantly affected by carbon and nitrogen sources, as well as pH (Barad et al., ; Kumar et al., ; Xia et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that the general inductor of fungal secondary metabolism biosynthesis, LaeA, is required for the production of not only patulin, but also other putative SMs produced by P. expansum , and contributes to virulence on apples (Kumar et al., ). In addition to LaeA, other regulatory proteins known to impact natural product biosynthesis in fungi, including transcription factors CreA, AreA and PacC associated with broad responses to carbon availability, nitrogen availability and pH, respectively, have been shown to be expressed during the biosynthesis of patulin, which is significantly affected by carbon and nitrogen sources, as well as pH (Barad et al., ; Kumar et al., ; Xia et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Protein signals in response to mycotoxin production have been used as biomarkers for the enhancement of plant resistance as well as fungal stress tolerance that contributes to interactions between host-pathogen [ 275 , 276 ]. Degola et al [ 277 ] documented the modification of sclerotial production of cuminaldehyde thiosemicarbazone, an inhibitor of AFTs biosynthesis in A. flavus .…”
Section: Omics Tools For Mycotoxin Detectionmentioning
confidence: 99%
“…For proteomics studies on PAT, we identified four articles after researching PubMed using proteomics and PAT as keywords. Most of the studies identified were investigating the proteome changes in Penicillium expansum during spore germination [ 164 ] and fungal development on different media to investigate the pathogen-host interaction mechanism [ 165 ]. The discovery of proteins signals in response for mycotoxin production and was used as biomarkers, which is valuable information for the researcher to improve plant resistance and stress tolerance of host plants against fungal contamination [ 166 ].…”
Section: Proteomics Approachmentioning
confidence: 99%